2010
DOI: 10.1088/0004-637x/725/1/605
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon and Emission Line Ratios in Active Galactic Nuclei and Starburst Galaxies

Abstract: We study the polycyclic aromatic hydrocarbons (PAH) bands, ionic emission lines, and midinfrared continuum properties, in a sample of 171 emission line galaxies taken from the literature plus 15 new active galactic nucleus (AGN) Spitzer spectra. We normalize the spectra at λ = 23µm and grouped them according to the type of nuclear activity. The continuum shape steeply rises for longer wavelengths and can be fitted with a warm blackbody distribution of T ∼ 150 -300K. The brightest PAH spectral bands (6.2, 7.7, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 37 publications
9
77
1
13
Order By: Relevance
“…The absorption features of this very luminous Sy1 galaxy, which is located at 128.6 Mpc (Scott et al 2004), are consistent with the presence of a warm absorber, most likely a dusty torus (Ebrero et al 2010). Moreover, weak PAH emission features have been independently observed in Mrk 279 by different groups (Santos-Lleó et al 2001;Sales et al 2010).…”
Section: Sourcesupporting
confidence: 77%
See 1 more Smart Citation
“…The absorption features of this very luminous Sy1 galaxy, which is located at 128.6 Mpc (Scott et al 2004), are consistent with the presence of a warm absorber, most likely a dusty torus (Ebrero et al 2010). Moreover, weak PAH emission features have been independently observed in Mrk 279 by different groups (Santos-Lleó et al 2001;Sales et al 2010).…”
Section: Sourcesupporting
confidence: 77%
“…Mrk 279 Gu & Huang (2002) 2001, 2007; Sales et al 2010Sales et al , 2013. The first two entries are Seyfert 1 (Sy1) AGNs, while the others are classified as Seyfert 2 (Sy2).…”
Section: Sourcementioning
confidence: 99%
“…This feature is strong and can be used as a reliable indicator for SF activity. Recent studies have shown that the ratio between the 11.3‐ and 7.7‐μm features in AGNs may differ significantly from those observed in SF galaxies (Diamond‐Stanic & Rieke 2010; Sales, Pastoriza & Riffel 2010). To further test this issue, we compared the luminosity ratio of the 11.3‐ and 7.7‐μm features in our sample to our SF templates.…”
Section: Spectral Decompositionmentioning
confidence: 96%
“…Several models predict the impact of radiation on the ionization and grain sizes of PAHs (Li & Draine 2001;Draine & Li 2007). Although the relations between the PAH features and their environments are not completely understood (Sadjadi et al 2015;, empirically we measure low EQW[PAH 6.2 µm] in galaxies with AGN (Smith et al 2007;Sales et al 2010). This property is a powerful diagnostic of the AGN's contribution to the MIR emission.…”
Section: Introductionmentioning
confidence: 96%